Negative effects of phosphorus addition outweigh effects of arbuscular mycorrhizal fungi and nitrogen addition on grassland temporal stability in the eastern Eurasian desert steppe - Xin Yang; Yuyue Li; Ruize Liang; Bo Ji; Zhanjun Wang; Hongmei Wang; Yue Shen (Ecology and Evolution, 2023)
Abstract The temporal stability of grassland plant communities is substantially affected by soil nutrient enrichment. However, the potential main and interactive effects of arbuscular mycorrhizal fungi (AMF) and soil nitrogen (N) and phosphorus (P) enrichment on the stability of plant productivity have not yet been clarified. We combined a three‐year in situ field experiment to assess the impacts of soil fertilization and AMF on the stability of plant productivity. P addition decreased the stability of plant productivity by increasing the standard deviation relative to the mean of plant productivity. However, compared to species richness, the stability of C3 grasses and other functional groups asynchrony were the most important drivers changing the stability of plant productivity. The negative impacts of P addition overrode the impacts of AMF on the stability of plant productivity. Overall, our study suggests the importance of soil nutrient availability over AMF in terms of shaping the stability of plant productivity. Our results also suggest that three‐year anthropogenic soil nutrient enrichment could reduce the stability of plant communities in grassland regardless of AMF in the P‐limited grassland ecosystem.